2014
DOI: 10.1513/annalsats.201402-050as
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Management of Lung Infections in Cystic Fibrosis. I. The Microbiome, Methicillin-Resistant Staphylococcus aureus, Gram-Negative Bacteria, and Multiple Infections

Abstract: Despite significant advances in treatment strategies targeting the underlying defect in cystic fibrosis (CF), airway infection remains an important cause of lung disease. In this two-part series, we review recent evidence related to the complexity of CF airway infection, explore data suggesting the relevance of individual microbial species, and discuss current and future treatment options. In Part I, the evidence with respect to the spectrum of bacteria present in the CF airway, known as the lung microbiome is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
185
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 75 publications
5
185
0
4
Order By: Relevance
“…The results confirmed that when grown as biofilms, these bacteria, like others, exhibited higher tolerance to antibiotics (9,16). The availability of aerosolized formulations of antibiotics, however, allows for higher pulmonary concentrations to be achieved in patients (10). All of the antibiotics tested in our study are either commercially available or in phase III study for aerosolization in CF patients, and the concentrations tested represent those achievable in the lungs after aerosolization.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The results confirmed that when grown as biofilms, these bacteria, like others, exhibited higher tolerance to antibiotics (9,16). The availability of aerosolized formulations of antibiotics, however, allows for higher pulmonary concentrations to be achieved in patients (10). All of the antibiotics tested in our study are either commercially available or in phase III study for aerosolization in CF patients, and the concentrations tested represent those achievable in the lungs after aerosolization.…”
supporting
confidence: 80%
“…Antimicrobial susceptibility testing was performed on isolates grown planktonically and as biofilms for amikacin, aztreonam, colistin, levofloxacin, and tobramycin, as previously described (8,9). Five A. xylosoxidans CF isolates with intermediate biofilm inhibitory concentrations (BICs) (defined as Յ800 g/ml tobramycin, representing the mean peak sputum concentration of aerosolized tobramycin [10]) and another 5 isolates from the same species but with high BICs (Ͼ800 g/ml tobramycin) were selected for further study in the biofilm slide chamber model. After 48 h of growth, biofilms were treated with various concentrations of tobramycin (0, 8, 400, a "Other species" includes A. denitrificans (n ϭ 3), A. dolens (n ϭ 5), A. insolitus (n ϭ 5), and A. ruhlandii (n ϭ 5).…”
mentioning
confidence: 99%
“…Therefore, where appropriate, we will refer the reader to recent, in-depth reviews of CF therapeutic strategies 8,9 for more information. Similarly, there have been a number of excellent reviews of CF respiratory microbiology and inflammation in general that the reader may find useful 1016 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for chronic lung diseases with frequent bacterial infections, such as cystic fibrosis (CF) and chronic obstructive pulmonary disease, airway microbiome dynamics have been associated with disease progression (Hunter et al, 2012, Pragman et al, 2012Huang et al, 2014). CF predisposes the respiratory tract to polymicrobial infections, and the frequent emergence of Pseudomonas aeruginosa is associated with a reduction in bacterial richness (Lynch and Bruce, 2013;Chmiel et al, 2014). Phenotype and virulence of P. aeruginosa are affected by interactions with the host and cohabiting microbes (Sibley et al, 2008a;Hunter et al, 2012;Venkataraman et al, 2014;Whiteson et al, 2014).…”
mentioning
confidence: 99%